2018
DOI: 10.4314/sokjvs.v16i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of African trypanosomosis in cattle and sheep in Bassa local government area of Plateau State, Nigeria

Abstract: A cross-sectional study to determine the prevalence of trypanosomosis in Bassa Local Government Area of Plateau State was carried out on 462 animals (361 cattle and 101 sheep) purposively selected. Blood samples were examined for trypanosomes and the packed cell volume was determined. Biconical traps were set to catch biting flies which were later dissected. The body condition scores of the selected animals were also noted. Out of the 462 blood samples examined, 22 (4.8%) tested positive for trypanosomes. Shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
7
3
0
Order By: Relevance
“…Age related prevalence as shown in table 3 revealed that young cattle below 3 years were more infected than cattle above 3 years old. This finding corroborates Idehen et al (15) assertion that younger animals are more prone to trypanosome infection than their adult counterparts. This observation that younger animals were more infected by trypanosome species than the adult ones is statistically significant (p< 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Age related prevalence as shown in table 3 revealed that young cattle below 3 years were more infected than cattle above 3 years old. This finding corroborates Idehen et al (15) assertion that younger animals are more prone to trypanosome infection than their adult counterparts. This observation that younger animals were more infected by trypanosome species than the adult ones is statistically significant (p< 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, the husbandry practices adopted by the herds owners in the treatment of their sick animals and This study has also shown that Trypanosoma vivax was the dominant species seen with aproportion of 81.1% prevalent rate. The finding is consistent with Fasanmi et al (17) assertion that T. vivax has the highest prevalent rate of 66.67% and Idehen et al (15) with T. vivax having 86.4% prevalent rate in their survey carried out.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The authors declare that they have no competing interests. [4,5,48,171,173-177,180,182,184,185,49,187-196,50,197-200,202,203,205-208,51,209-212,214-21 227,229,230,232,235,53,236,238-243,246-248,54,249-258,57,259,261-269,58,270,271,273,274,276-281,59,282,283,6,61,62,64-66,68-71,73,12,74-78,80-83,85,14,86-88,90-95,99,40,101-103,105,106,108,109,111,113,114,44,116,118,122,123,125-127,129-131,45,132,134-136,138 [6,7,128,137,140,143,144,150,158,168,179,193,55,197,201,204,211,213,218,221,225,234,237,57,239 [7,57,245,246,67,68,133,158,168,197,198,201 [6,7,128,134,137,140,143,144,…”
Section: Competing Interestsmentioning
confidence: 99%
“…The authors declare that they have no competing interests. [6,7,128,137,140,143,144,150,158,168,179,193,55,197,201,204,211,213,218 [6,7,128,134,137,140,143,144,168,197,201,213,55,221,225,234,248,272,57,60,79,98,116,118,120] Small ruminants Kenya, Nigeria 988 69 [89,110,227] Water buffalo Brazil, Venezuela 2144 509 [116,118,119,…”
Section: Consent For Publicationmentioning
confidence: 99%